Gene expression in the chicken caecum in response to infections with non-typhoid Salmonella - Rychlik, Ivan; Elsheimer-Matulova, Marta; Kyrova, Kamila (Veterinary research, 2014)
Chickens can be infected with Salmonella enterica at any time during their life. However, infections within the first hours and days of their life are epidemiologically the most important, as newly hatched chickens are highly sensitive to Salmonella infection. Salmonella is initially recognized in the chicken caecum by TLR receptors and this recognition is followed by induction of chemokines, cytokines and many effector genes. This results in infiltration of heterophils, macrophages, B- and T-lymphocytes and changes in total gene expression in the caecal lamina propria. The highest induction in expression is observed for matrix metalloproteinase 7 (MMP7). Expression of this gene is increased in the chicken caecum over 4000 fold during the first 10 days after the infection of newly hatched chickens. Additional highly inducible genes in the caecum following S. Enteritidis infection include immune responsive gene 1 (IRG1), serum amyloid A (SAA), extracellular fatty acid binding protein (ExFABP), serine protease inhibitor (SERPINB10), trappin 6-like (TRAP6), calprotectin (MRP126), mitochondrial ES1 protein homolog (ES1), interferon-induced protein with tetratricopeptide repeats 5 (IFIT5), avidin (AVD) and transglutaminase 4 (TGM4). The induction of expression of these proteins exceeds a factor of 50. Similar induction rates are also observed for chemokines and cytokines such as IL1β, IL6, IL8, IL17, IL18, IL22, IFNγ, AH221 or iNOS. Once the infection is under control, which happens approx. 2 weeks after infection, expression of IgY and IgA increases to facilitate Salmonella elimination from the gut lumen. This review outlines the function of individual proteins expressed in chickens after infection with non-typhoid Salmonella serovars.
Keywords: nemoci drůbeže; Salmonella Infections, Animal; ptačí proteiny; exprese genu; Poultry Diseases; kur domácí; Animals; Cecum; Avian Proteins; cékum; salmonelová infekce u zvířat; Gene Expression; Chickens; zvířata; Salmonella